2012
DOI: 10.1109/tro.2011.2165372
|View full text |Cite
|
Sign up to set email alerts
|

Activity-Based Estimation of Human Trajectories

Abstract: Abstract-We present a novel approach to incrementally determine the trajectory of a person in 3D based on its motions and activities in real-time. In our algorithm, we estimate the motions and activities of the user given the data obtained from a motion capture suit equipped with several inertial measurement units (IMUs). These activities include walking up and down staircases as well as opening and closing doors. We interpret the first two types of activities as motion constraints and door handling events as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…• Activity-based SLAM assumes that some human activities only occur at specific locations. For mapping runs in three large buildings, Grzonka et al showed that the detection of stair climbing and door opening enables to avoid long-term error accumulation of PDR [11]. In daily life at home, these activities occur infrequently (e.g.…”
Section: Related Workmentioning
confidence: 99%
“…• Activity-based SLAM assumes that some human activities only occur at specific locations. For mapping runs in three large buildings, Grzonka et al showed that the detection of stair climbing and door opening enables to avoid long-term error accumulation of PDR [11]. In daily life at home, these activities occur infrequently (e.g.…”
Section: Related Workmentioning
confidence: 99%
“…We note that, some research studies provide a solution for large buildings such as office buildings and commercial complex to generate floorplan images by using crowdsourcing techniques. Although the SLAM techniques [29], [30], [31] or c 2019 Information Processing Society of Japan PDR techniques [32], [33] to trace human walking paths can be used to construct the floorplan images, the drawback is inaccuracy caused by accumulated distance and direction errors caused by orientation change of smartphones while they are walking, inaccuracy of stride length estimation and some other unexpected noise.…”
Section: Indoor Floorplanmentioning
confidence: 99%
“…The method is focused on simplified data collection to compose a map of the environment. In an application area such as building a map of the lo- cal environment, simplified measurements based on human skill are useful because of the high mobility of humans in unprepared, unobserved, and uncertain environments [17,18]. In the following sections, we introduce the data collection methods for constructing the map, including the fingerprints of the wireless LAN signals and the 3-D natural feature points.…”
Section: Localization Of Mobile Client Based On Data Fusion Of Wirelementioning
confidence: 99%